Implementasi Pembangunan Berbasis Rukun Tetangga (PBRT): Pengalaman Tata Kelola Pemerintahan di Kabupaten Sumbawa Barat - Johan Wahyudi (Departemen Ilmu Pemerintahan Fisip Unhas, 2016)
Abstract: This paper will show an example of governance practices and innovations of good governance (good practice) in large framework of good governance in Indonesia. This paper describes how the community is involved in the development process. By using the perspective of the ladder of participation from Bovaird and Loffler (2004) or participation ladder in the development process, the local district government of West Sumbawa successfully carry out the spirit of good governance at the grass roots level in the community. Key Words: Good practice; ladder of participation; governance inovation; Abstraksi: Tulisan ini akan menunjukkan salah satu contoh praktik tata kelola dan inovasi tata pemerintahan yang baik (good practice) dalam kerangka besar good governance di Indonesia. Paper ini menggambarkan bagaimana masyarakat dilibatkan dalam proses pembangunan. Dengan menggunakan perspektif ladder of participation Bovaird dan Loffler (2004) atau tangga partisipasi dalam proses pembangunan, pemerintah daerah Kabupaten Sumbawa Barat berhasil melaksanakan spirit good governance di level akar rumput di masyarakat. Kata-kata Kunci: Good practice; ladder of participation; inovasi tata kelola;